GLI2 promoter hypermethylation in saliva of children with a respiratory allergy - Sabine A. S. Langie; Matthieu Moisse; Katarzyna Szarc vel Szic; Ellen Van Der Plas; Gudrun Koppen; Sofie De Prins; Tijs Louwies; Vera Nelen; Guy Van Camp; Diether Lambrechts; Greet Schoeters; Wim Vanden Berghe; et al. (Clinical Epigenetics, 2018)
Abstract Background The prevalence of respiratory allergy in children is increasing. Epigenetic DNA methylation changes are plausible underlying molecular mechanisms. Results Saliva samples collected in substudies of two longitudinal birth cohorts in Belgium (FLEHS1 & FLEHS2) were used to discover and confirm DNA methylation signatures that can differentiate individuals with respiratory allergy from healthy subjects. Genome-wide analysis with Illumina Methylation 450K BeadChips revealed 23 differentially methylated gene regions (DMRs) in saliva from 11y old allergic children (N=26) vs. controls (N=20) in FLEHS1. A subset of 7 DMRs was selected for confirmation by iPLEX MassArray analysis. First, iPLEX analysis was performed in the same 46 FLEHS1 samples for analytical confirmation of the findings obtained during the discovery phase. iPLEX results correlated significantly with the 450K array data (P <0.0001) and confirmed 4 out of the 7 DMRs. Aiming for additional biological confirmation, the 7 DMRs were analyzed using iPLEX in a substudy of an independent birth cohort (FLEHS2; N=19 cases vs. 20 controls, aged 5 years). One DMR in the GLI2 promoter region showed a consistent statistically significant hypermethylation in individuals with respiratory allergy across the two birth cohorts and technologies. In addition to its involvement in TGF-β signaling and T-helper differentiation, GLI2 has a regulating role in lung development. Conclusion GLI2 is considered an interesting candidate DNA methylation marker for respiratory allergy.